Molecular Mechanisms Underlying the Biosynthesis of Melatonin and Its Isomer in Mulberry - Zheng, Sha; Zhu, Yingxue; Liu, Changying; Zhang, Shuai; Yu, Maode; Xiang, Zhonghuai; Fan, Wei; Wang, Shuchang; Zhao, Aichun (Frontiers in Plant Science, 2021)
Mulberry (Morus alba L.) leaves and fruit are traditional Chinese medicinal materials with anti-inflammatory, immune regulatory, antiviral and anti-diabetic properties. Melatonin performs important roles in the regulation of circadian rhythms and immune activities. We detected, identified and quantitatively analyzed the melatonin contents in leaves and mature fruit from different mulberry varieties. Melatonin and three novel isoforms were found in the Morus plants. Therefore, we conducted an expression analysis of melatonin and its isomer biosynthetic genes and in vitro enzymatic synthesis of melatonin and its isomer to clarify their biosynthetic pathway in mulberry leaves. MaASMT4 and MaASMT20, belonging to class II of the ASMT gene family, were expressed selectively in mulberry leaves, and two recombinant proteins that they expressed catalyzed the conversion of N-acetylserotonin to melatonin and one of three isomers in vitro. Unlike the ASMTs of Arabidopsis and rice, members of the three ASMT gene families in mulberry can catalyze the conversion of N-acetylserotonin to melatonin. This study provides new insights into the molecular mechanisms underlying melatonin and its isomers biosynthesis and expands our knowledge of melatonin isomer biosynthesis.